Crimea and punishment: the impact of sanctions on Russian economy and economies of the euro area - Konstantin A. Kholodilin; Aleksei Netšunajev (Baltic Journal of Economics, 2019)
The conflict between Russia and Ukraine that started in March 2014 led Western countries and Russia to impose economic sanctions on each other, including the euro zone members. The paper investigates the impact of the sanctions on the real side of the economies of Russia and the euro area. The effects of sanctions are analyzed with a structural vector autoregression. To pin down the effect we are interested in, we include an index that measures the intensity of the sanctions in the model. The sanction shock is identified and separated from the oil price shock by narrative sign restrictions. We find weak evidence that Russian and euro area GDPs declined as a result of the sanctions. The effects of the sanctions are also small for the real effective exchange rate.
Keywords: C32; F51; 330; political conflict; sanctions; economic growth; Russia; euro area; structural vector autoregression